Geochemical and mineralogical constraints in iron ore tailings limit soil formation for direct phytostabilization - Wu, S.; Liu, Y.; Southam, G.; Robertson, L.; Chiu, T.; Cross, Adam; Dixon, Kingsley; Stevens, J.; Zhong, H.; Chan, T.; Lu, Y.; Huang, L. (Elsevier, 2019)
© 2018 Elsevier B.V. The present study aimed to characterize key physico-chemical and mineralogical attributes of magnetite iron (Fe) ore tailings to identify potential constraints limiting in situ soil formation and direct phytostabilization. Tailings of different age, together with undisturbed local native soils, were sampled from a magnetite mine in Western Australia. Tailings were extremely alkaline (pH > 9.0), with a lack of water stable aggregate and organic matter, and contained abundant primary minerals including mica (e.g., biotite), with low specific surface area (N2-BET around 1.2 m2 g-1). These conditions remained relatively unchanged after four years’ aging under field conditions. Chemical extraction and spectroscopic analysis [e.g., X-ray diffraction (XRD) and synchrotron-based Fe K edge X-ray absorption fine structure spectroscopy (XAFS) analysis] revealed that the aging process decreased biotite-like minerals, but increased hematite and magnetite in the tailings. However, the aged tailings lacked goethite, a compound abundant in natural soils. Examination using backscattered-scanning electron microscope - energy dispersive X-ray spectrometry (BSE-SEM-EDS) revealed that aged tailings contained discrete sharp edged Fe-bearing minerals that did not physically integrate with other minerals (e.g., Si/Al bearing minerals). In contrast, Fe minerals in native soils appeared randomly distributed and closely amassed with Si/Al rich phyllosilicates, with highly eroded edges. The lack of labile organic matter and the persistence of alkaline-saline conditions may have significantly hindered the bioweathering of Fe-minerals and the biogenic formation of secondary Fe-minerals in tailings. However, there is signature that a native pioneer plant, Maireana brevifolia can facilitate the bioweathering of Fe-bearing minerals in tailings. We propose that eco-engineering inputs like organic carbon accumulation, together with the introduction of functional microbes and pioneer plants, should be adopted to accelerate bioweathering of Fe-bearing minerals as a priority for initiating in situ soil formation in the Fe ore tailings.